2020
DOI: 10.1021/jacs.0c11925
|View full text |Cite
|
Sign up to set email alerts
|

Selective Construction of Very Large Stacking-Interaction-Induced Molecular 818 Metalla-knots and Borromean Ring Using Curved Dipyridyl Ligands

Abstract: Two molecular metalla-knots containing over 500 non-hydrogen atoms (especially 16 RhIII ions) and one molecular Borromean ring were obtained in high yields facilitated by multiple intermolecular interactions between their components. The syntheses rely on the strategic selection of the nonlinear dipyridyl ligand 2,7-di­(pyridin-4-yl)-9H-fluorene (L 1 ) as precursor, and the structures of the assemblies were confirmed by detailed X-ray crystallographic analysis. Subsequently, replacing L 1 with the bulkier l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…A similar backbone design was reported to lead to Fe-based helicates and tetrahedra, 57 60 as well as knots and Borromean rings. 61 …”
mentioning
confidence: 99%
“…A similar backbone design was reported to lead to Fe-based helicates and tetrahedra, 57 60 as well as knots and Borromean rings. 61 …”
mentioning
confidence: 99%
“…Recently, our group reported the selective construction of molecular 8 18 metalla‐knots and a Borromean ring using curved dipyridyl ligands, and we found that increasing the steric hindrance of the dipyridyl ligand can weaken π−π stacking interactions, leading instead to the formation of simple tetranuclear metallacycles [39] . This work inspired us to envision whether replacing smaller ligands with bulkier ligands could give rise to more complex structural changes rather than merely the formation of simple monocyclic compounds.…”
Section: Introductionmentioning
confidence: 97%
“…[3,15,[20][21][22][23][24][25] As a complementary method to template-based syntheses, coordination-driven self-assembly has become an essential -and in many ways advantageous -approach to the high-yielding construction of a range of molecular metalla-knots and -links over the last decade. [4,14,15,23,[26][27][28][29][30][31][32] Focusing on the latter approach, our group has taken advantage of half-sandwich organometallic fragments together with ligands having different geometrical characteristics to construct a family of molecular metalla-knots and -links featuring complex and exquisite topologies, [30,[33][34][35][36][37][38][39] in addition to exploring their applications in the separation of halogenated aromatics [40] and stimuli-responsive topological transformations. [41][42][43] Recently, our group reported the selective construction of molecular 8 18 metalla-knots and a Borromean ring using curved dipyridyl ligands, and we found that increasing the steric hindrance of the dipyridyl ligand can weaken πÀ π stacking interactions, leading instead to the formation of simple tetranuclear metallacycles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations